Visceral artery aneurysms: an institutional review - Sapkota, Rajan; Ghimire, B; Lakhey, PJ; Ghimire, R K; Shrestha, U K (Journal of Society of Surgeons of Nepal, 2017)
Methods: It is a retrospective review of prospectively kept data of patients treated for visceral artery aneurysms in Tribhuvan University Teaching Hospital and Manmohan Cardiothoracic Vascular and Transplant Center from 1997 to 2009.Results: Fifteen patients were diagnosed with 16 visceral artery aneurysms. These consisted of 7 splenic (in 6 patients), 4 hepatic, 2 superior mesenteric, 1 gastroduodenal, and 1 renal artery aneurysms. There were 14 symptomatic patients including 4 who presented with rupture. Commonest presenting symptom was pain abdomen (14/15), followed by gastrointestinal bleed (6/15) and mass abdomen (5/15). The diagnosis was made with the help of CECT of abdomen in 13 patients, which was confirmed by conventional angiography in three patients. In two patients with obscure GI bleeding, diagnosis was clinched by conventional angiogram. Eight patients were treated only surgically, with three mortality. Transcatheter embolization alone was used in 5 patients. Two patients were treated with combination of surgical and endovascular therapy. One patient with superior mesenteric artery aneurysm in whom nothing could be done during laparotomy died six months later. Average follow up duration was one year.Conclusion: Splenic artery remains the most commonly afflicted vessel among the visceral artery aneurysms. The VAAs can be treated surgically or with endovascular means with fair success, although the best mode of treatment needs to be individualized.Journal of Society of Surgeons of NepalVol. 17, No. 2, 2014, Page: 3-6